Adolescent use of urban parks and their social environment consequences - Zohreh Mahdiar,; Melasutra Md Dali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Parks increase their users’ health and well-being because they offer settings suitable for physical activity, social interaction, enjoying nature, etc. Applying the socio-physical approach, “park use” behaviour is influenced by several environmental characteristics, including physical environment, social environment, and cultural environment. This study seeks to understand the influence of park social environment based on the perspectives of adolescent park users aged15-18. A qualitative study (interviews) with 17 adolescents aged 15-18 (including male and female) shows that the social environment of an urban park plays an important role among adolescents. The research contributes to understanding how the social environment influence on park use and thus assists urban planners in measuring key targeted actions to improve the perception of social environment among adolescents to increase park use.